2008
DOI: 10.1080/19396360802379073
|View full text |Cite
|
Sign up to set email alerts
|

Plants Used in Chinese Medicine for the Treatment of Male Infertility Possess Antioxidant and Anti-Oestrogenic Activity

Abstract: In this study Chinese herbs commonly used in the treatment of male infertility were investigated for relevant biochemical activity. Male factor infertility predominantly arises via barriers to, or defects in, spermatogenesis. The process of spermatogenesis is under strict endocrine control; in addition oxidative stress has been implicated in male infertility with significant levels of reactive oxygen species detected in 25% of infertile males. A total of 37 individual herbs and seven herb decoctions used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…These include: (i) Klinefelter syndrome patients; (ii) patients with cytogenetically visible structural chromosome aberrations; (iii) NOA patients (should enough sperm be available for treatment and screening); (iv) oligoasthenoteratozoospermic patients; (v) patients with a history of unexplained recurrent pregnancy loss or repeated in vitro fertilization or intracytoplamic sperm injection failure; and (vi) patients with very high levels macrocephalic, multinucleated and multiflagellate sperm. 21,[80][81][82][83] Performing routine sperm aneuploidy screening in these patients will enable a more individualized risk assessment of aneuploid offspring. For example, the genetic counseling of a patient with low levels of sperm aneuploidy (comparable to fertile controls) will be very different to that of an individual with 40% aneuploid sperm.…”
Section: Issues Associated With Identifying Mutations In Human Meiotimentioning
confidence: 99%
See 1 more Smart Citation
“…These include: (i) Klinefelter syndrome patients; (ii) patients with cytogenetically visible structural chromosome aberrations; (iii) NOA patients (should enough sperm be available for treatment and screening); (iv) oligoasthenoteratozoospermic patients; (v) patients with a history of unexplained recurrent pregnancy loss or repeated in vitro fertilization or intracytoplamic sperm injection failure; and (vi) patients with very high levels macrocephalic, multinucleated and multiflagellate sperm. 21,[80][81][82][83] Performing routine sperm aneuploidy screening in these patients will enable a more individualized risk assessment of aneuploid offspring. For example, the genetic counseling of a patient with low levels of sperm aneuploidy (comparable to fertile controls) will be very different to that of an individual with 40% aneuploid sperm.…”
Section: Issues Associated With Identifying Mutations In Human Meiotimentioning
confidence: 99%
“…One such example of a personalized approach was previously published demonstrating in a small cohort of men, a significant reduction in sperm aneuploidy levels coincident with traditional Chinese herbal medicine treatment for male infertility. 82,92 The ultimate goal has to be the ability to offer valuable clinical prognostic options with appropriate treatment options as a result of the genetic basis of the infertility phenotype. This clearly remains a question for basic science at present and for the immediate future.…”
Section: Future Clinical Perspectives For Male Factor Infertilitymentioning
confidence: 99%
“…It has been suggested that non-disjunction of specific chromosome pairs may be associated with specific semen parameters and that screening for sperm aneuploidy could become a prognostic test for couples undergoing ICSI [Petit et al, 2005;Durakbasi-Dursun et al, 2008;Sanchez-Castro et al, 2009]. There may even be avenues for possible therapy [Tempest et al, 2008].…”
Section: Sperm Disomy Levels and Infertilitymentioning
confidence: 99%
“…The percentage of infertility attributed to males has reached 50% (1). Certain Chinese herbal decoctions have been reported to be efficacious in infertility treatment (2,3). However, the active mechanisms of these remedies remain unknown.…”
Section: Introductionmentioning
confidence: 99%